Effects of anticonvulsant drugs on thyroid hormones in epileptic children - Deda, Gülhis; Akıncı, Ayşehan; Teziç, Tahsin; Karagöl, Uğur (The Turkish Journal of Pediatrics, 1992)
Serum total and free thyroid hormones, reverse T3 (rT3), thyroxin binding globulin (TBG) and thyroid stimulating hormone (TSH) concentrations were measured in 35 epileptic patients receiving anticonvulsants (phenobarbitone, phenytoin). There was a significant reduction found in total thyroxine (TT4), free thyroxine (FT4), total triiodothyronine (TT3), free triiodothyronine (FT3) and rT3 in the group treated with phenytoin. The thyroid hormone levels were within normal limits in the group receiving phenobarbitone.
Keywords: anticonvulsant drugs; thyroid functions